2015
DOI: 10.1186/s12936-015-0559-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of non-instrumented nucleic acid amplification by loop-mediated isothermal amplification (NINA-LAMP) for the diagnosis of malaria in Northwest Ethiopia

Abstract: BackgroundMalaria is a major public health problem in sub-Saharan African countries including Ethiopia. Early and accurate diagnosis followed by prompt and effective treatment is among the various tools available for prevention, control and elimination of malaria. This study aimed to evaluate the performance of non-instrumented nucleic acid amplification loop-mediated isothermal amplification (NINA-LAMP) compared to standard thick and thin film microscopy and nested PCR as gold standard for the sensitive diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 29 publications
6
88
0
Order By: Relevance
“…Giemsa staining and microscopy was performed as described previously. 11 Only those with mono-infection with P. falciparum were included in this study. Finger prick blood samples were collected on Whatman 903 filter paper (GE Healthcare, Mississauga, Canada) at the time of diagnosis, air-dried, individually inserted in a zip-lock bag, and transported to University of Calgary, Canada, for molecular analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Giemsa staining and microscopy was performed as described previously. 11 Only those with mono-infection with P. falciparum were included in this study. Finger prick blood samples were collected on Whatman 903 filter paper (GE Healthcare, Mississauga, Canada) at the time of diagnosis, air-dried, individually inserted in a zip-lock bag, and transported to University of Calgary, Canada, for molecular analysis.…”
mentioning
confidence: 99%
“…Genomic DNA extraction from the filter paper blood spots was performed as described previously in a study. 11 Plasmodium falciparum kelch 13 was amplified from the genomic DNA samples using nested polymerase chain reaction (PCR) with slight modification.…”
mentioning
confidence: 99%
“…The duration of the power delivery can be extended as these devices use up to 20x more MgFe for a single test (and consequently, produce as much hydrogen) than the amount used in the fuel cells presented here. [39][40][41][42] This approach implies reusability of the fuel cells for more than one measurement, thus reducing the overall cost per test.…”
Section: Integration Of Hydrogen Fuel Cell Stripmentioning
confidence: 99%
“…the corrosion of magnesium iron particles. [36][37][38][39][40][41][42] This chemistry is very convenient, as it , requires only the addition of water to achieve 100°C (a reason why it has also been widely used to heat portable meals). During the course of the chemical reaction the magnesium is oxidized, releasing hydrogen gas as a byproduct, which previously was simply vented off to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The LAMP assays commonly present diagnostic efficacy similar to the nested PCR assays, considered by many articles the gold standard. [41][42][43] These reports showed that LAMP assays enable detection of P. falciparum and P. vivax at the species level and diagnose asymptomatic infections or low parasitic loads. 41,43,44 Molecular diagnosis may also facilitate the detection and identification of malaria cases in nonendemic countries, where individuals may become infected when traveling for business or tourism.…”
Section: Malariamentioning
confidence: 99%